2012
DOI: 10.1074/jbc.m112.405100
|View full text |Cite
|
Sign up to set email alerts
|

Tic22 Is an Essential Chaperone Required for Protein Import into the Apicoplast

Abstract: Background: Tic22 is a core protein import machinery component of chloroplasts and apicoplasts. Results: Tic22 is a chaperone, required for parasite survival and for protein import in the apicoplast. Conclusion: Tic22 lies between the plastid membranes, maintaining imported proteins unfolded for translocation. Significance: Chaperones which hold proteins in an unfolded state are central to membrane translocation systems and Tic22 plays this role in plastids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 35 publications
(67 reference statements)
5
59
0
Order By: Relevance
“…Tic22 from the apicomplexan Toxoplasma gondii has been shown to have chaperone-like activity in vitro (42), suggesting that Tic22 also may act as an IMS chaperone for translocating precursors in chloroplasts. Mutants lacking both Tic22 homologs in Arabidopsis are import-deficient, and it was recently shown that Tic22 protein levels are up-regulated in plants expressing POTRA-deleted versions of Toc75 (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tic22 from the apicomplexan Toxoplasma gondii has been shown to have chaperone-like activity in vitro (42), suggesting that Tic22 also may act as an IMS chaperone for translocating precursors in chloroplasts. Mutants lacking both Tic22 homologs in Arabidopsis are import-deficient, and it was recently shown that Tic22 protein levels are up-regulated in plants expressing POTRA-deleted versions of Toc75 (15).…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, insulin B aggregation is induced by the reduction of A chain-B chain disulfide bonds with 20 mM DTT, and aggregation is measured over time by light scattering at 360 nm (42). In our system, chaperone activity was assessed by the ability of the added POTRAs to prevent B chain aggregation and the resulting reduction in light scattering.…”
Section: Potra2-3 Mediates An Interaction With the Model Chloroplastmentioning
confidence: 99%
“…To localize TgTom40, we amplified the 3Ј region with primers 1 and 2 (Table 1) and inserted this into the vector pHA 3 .LIC.DHFR (a kind gift from Michael White, University of South Florida) by ligation-independent cloning (LIC), as described previously (50), before linearization with EcoRV, transfection into ⌬ku80 strain parasites, and selection on pyrimethamine as described (52). To localize TgSam50, we amplified the open reading frame with primers 3 and 4, digested the resulting product with BglII and AvrII, ligated into the vector pBTM 3 (53), transfected into parasites, and selected on phleomycin as described (54). To localize TgTim22, we amplified the 3Ј region with primers 5 and 6, digested the resulting product with BglII and AvrII, ligated into pHH vector, a modified version of the pgCM3 vector described previously (55) that has a selectable marker for mycophenolic acid selection.…”
Section: Methodsmentioning
confidence: 99%
“…To generate a strain expressing the mitochondrial targeting sequence of TgHsp60 fused to c-Myc-tagged mouse DHFR, we digested the TgHsp60 leader sequence from the vector Hsp60-RFP in pBTR (58) with BglII and AvrII, ligated this into the equivalent sites of the vector mDHFR in pBTM 3 (53), transfected into the TgTom22 knockdown cell line, and selected on phleomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic molecular chaperones, Hsc70 and Hsp90, have been proposed to assist in delivery of preproteins to the TOC receptors, Toc34 and Toc159, and the intrinsic GTPase activities of the receptors initiate outer membrane translocation via the β-barrel membrane channel, Toc75 (2,3). Preprotein translocation occurs simultaneously through the TOC and TIC complexes with the assistance of Tic22, a chaperone in the intermembrane space (6,7), and the putative channel components, Tic20 and Tic21 (2,3). The TIC machinery interacts with three ATP-driven molecular chaperones in the stroma (3,5).…”
mentioning
confidence: 99%